Integrating Early Palliative Care for Patients With HIV: Provider and Patient Perceptions of Symptoms and Need for Services. (December 2015) - Lofgren, Sarah; Friedman, Rachel; Ghermay, Rahwa; George, Maura; Pittman, John Richard; Shahane, Amit; Zeimer, Dorothy; Del Rio, Carlos; Marconi, Vincent C.
Increasingly clinicians are using palliative care to address the symptomatic and psychosocial effects of disease often missed by routine clinical care, termed "early" palliative care. Within an inner-city medical center, we began a program to integrate early palliative care into HIV inpatient care. Patient symptom burden and desired services were assessed and compared to provider perceptions of patient's needs. From 2010-2012, 10 patients, with a median CD4+ T-cell count of 32.5 cells/μL, and 34 providers completed the survey. Providers ranked their patients' fatigue, sadness, anxiety, sexual dysfunction, and body image significantly higher than patients it for themselves. Patients ranked medical care, pharmacy, social work, physical therapy, and housing as significantly more important to them than providers estimated them to be. These differences may reflect the fact that physicians often overlook patients' unmet basic needs. Early palliative care may narrow this gap between providers' and patients' perceptions of needs through good communication and targeting barriers, such as housing instability, which are vital to overcome for consistent long-term follow up.